Analysing Perceptions of Sharia Law Students on the Khilafah in Indonesian State Islamic Universities - Joko Subando; Muhammad Kurniawan Budi Wibowo; Baehaqi; Firdos; Nur Aina Abdulah; Heni Satar Nurhaida (Balai Penelitian dan Pengembangan Agama Semarang, 2024)
Non-Indexed Publication